Pengaruh Lingkungan Keluarga Dan Proses Pembeljaran Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Wulan Purnamasari; A. Amiruddin Tawe; Herman Herman (Phinisi Integration Review, 2022)
Education is one of the essential things in life. In simple terms, education is a means that can free someone from ignorance, such as poverty, bondage, being easily deceived, narrow mindset, and so on. The National Education System states that national education aims to develop students’ potential to become human beings who believe and are pious. Interest in entrepreneurship can be seen from the willingness to work hard and diligently to achieve business progress, the willingness to bear various risks related to the business actions he does, the willingness to take new paths and ways, the willingness to live frugally, the willingness to experience. Based on this, the study aims to discover 1) the influence of the family environment on the entrepreneurial interest of economic education students at the Faculty of Economics in the State University of Makassar, 2) the influence of the entrepreneurship learning process on the entrepreneurial interest of economic education students at the Faculty of Economics in State University of Makassar, 3) the influence of the family environment and entrepreneurship learning process on the entrepreneurial interest of economic education students at the Faculty of Economics in State University of Makassar. The research method employed a survey research type with a quantitative approach. The study results indicate that there is an influence of the family environment on entrepreneurial interest. The test result shows that the count is greater than the ttable. There is an influence of the entrepreneurship learning process on entrepreneurial interest. The test result indicates that the account is greater than the ttable. The family environment and entrepreneurship learning process collectively influence entrepreneurial interest. The test result shows that the Account is greater than the Ftable. Therefore, the research hypothesis is accepted.